POLA KOMUNIKASI DRIVER OJEK ONLINE GRABBIKE PADA PELAYANAN CUSTOMER DI KOTA MALANG - Moh Amiruddin (INTAJ : Jurnal Penelitian Ilmiah, 2019)
Transportation is an important part of the daily activities of the community. Along with the rapid development of technology, transportation facilities have also developed, one of which is the emergence of online transportation. Grab is one of the online transportation applications that circulate in various regions in Indonesia. One of its features, GrabBike, is that drivers are the main center in terms of serving the customers. Therefore, a good communication is needed. Communication is often an obstacle for drivers in serving customers. It is necessary to know the communication patterns used by the drivers in communicating to the customers. This research is conducted using qualitative data collection through observation and interviews. the results obtained are that GrabBike online motorcycle taxi drivers using three communication patterns in service to customers including linear or one-way communication patterns, circular or two-way communication patterns, and helical or spiral communication patterns.